Herbert Caro nas cartas de Erico Veríssimo - Bordini, Maria da Glória (Contingentia, 2008)
Erico Verissimo’s letters to Herbert Caro, during the 1950s, offer a portrait of the translator of Thomas Mann, revealing his taste for music and movies as well as an insights in his role as a critic and confident of the Brazilian author.